Establishing a reproducible protocol for measuring index active extension strength. (February 2017) - Matter-Parrat, V.; Hidalgo Diaz, J. J.; Collon, S.; Salazar Botero, S.; Prunières, G.; Ichihara, S.; Facca, S.; Liverneaux, P.
The goal of this study was to establish a reproducible protocol to measure active extension strength in the index finger. The secondary objectives consisted in correlating the independent or associated index extension strength to the other fingers force of contraction of the extensor indicis propius with hand dominance. The population studied consisted of 24 healthy volunteers, including 19 women and 20 right-handed individuals. The independent and dependent index extension strength in each hand was measured three times with a dynamometer by three examiners at Day 0 and again at Day 7. Intra and inter-examiner reproducibility were, respectively, >0.90 and >0.75 in all cases. The independent extension strength was lower than the dependent one. There was no difference between the independent index extension strength on the dominant and non-dominant sides. The same was true for the dependent strength. Our results show that our protocol is reproducible in measuring independent and dependent index extension strength. Dominance did not come into account. Level of evidence: II